Efektivitas Dakwah Bil-Hal Melalui Gerakan Infaq Beras Bengkayang di Kecamatan Bengkayang - Nurul Khaerunnisa (UNISBA Press, 2021)
Abstract. Da'wah bil-hal is a da'wah that is carried out with real actions, This researcher tries to reveal the problem regarding Bil Da'wah in Bengkayang District, namely bil-hal da'wah carried out by the Gerakan Infaq Beras Movement. Gerakan Infaq Beras is a program of the Pasukan Amal Sholeh community. The choice of rice to be distributed is because rice is a staple for Indonesian society, the beneficiaries of this are Islamic boarding schools and orphanages. However, it is different in Bengkayang with the number of Muslim minorities, which is only 36.39% of the 32,141 people. With a minority number making it difficult to preach, this movement emerged as the beginning of the Islamic movement. After the existence of this movement, the effectiveness of this movement will be seen to introduce Islam. This research method is qualitative with descriptive analytical research and descriptive qualitative with data collection techniques using field observations, interviews, documentation to be further described in the form of reports. The results of his research are: (1) Da'wah activities in Bengkayang are not enough, especially for da'wah bil-hal (2) Invitation from Gerakan Infaq Beras to join by socializing directly to the place and through social media. (3) Da'wah bil-things done by the Infaq Movement rice is effective because it can achieve the desired goal. Keywords: Effectiveness, Da'wah bil-hal Infaq. Abstrak. Peneliti berusaha untuk mengungkapkan Tema mengenai “Efektifitas Dakwah Bil-hal melalui Gerakan Infaq Beras Bengkayang di Kecamatan Bengkayang”. yang dilakukan oleh Gerakan Infaq Beras Bengkayang. Gerakan Infaq Beras ini merupakan program dari komunitas Pasukan Amal Sholeh. Pemilihan beras untuk dibagikan, kepada Pesantren dan panti asuhan. Namun, di Bengkayang jumlah muslim minoritas, yaitu hanya 36,39 % di Kecamatan Bengkayang. Dengan jumlah minoritas membuat kesulitan untuk berdakwah, maka munculah gerakan ini. Melalui gerakan pembagian beras terlihat efektifitasnya untuk mengenalkan Islam. Penelitian ini adalah kualitatif dengan menggunakan metode deskriptif analitis, dengan teori Efektifitas. Teknik pengumpulan data mengunakan observasi di lapangan, wawancara, dokumentasi.. Hasil penelitian adalah: (1) Kegiatan dakwah di Bengkayang belum cukup banyak terutama untuk dakwah bil-hal (2) Ajakan dari Gerakan Infaq beras untuk bergabung dengan cara mensosialisasikan langsung ke tempat dan melalui media sosial. (3) Dakwah bil-hal yang dilakukan oleh Gerakan Infaq beras adalah efektiv karena dapat mencapai tujuan yang diinginkan. Kata Kunci: Efektivitas, Dakwah bil-hal, Infaq.